Magnetni monopoli v spinskem ledu - Pišljar, Jaka (Matrika, 2014)
Main characteristics of the magnetic monopoles, together with their magnetic field and the term Dirac string are summarized. Next, the properties of the frustrated systems are explained, as these are essential in further explanation of the spin ice materials. The spin ice materials are presented, as well as the magnetic interactions responsible for their physical properties. The effective magnetic monopoles emerging in spin ice are introduced through the dumbbell model, where magnetic dipoles are replaced by pairs of magnetic monopoles. In conclusion, the equlibrium state of spin ice in a magnetic field is discussed.
Keywords: magnetic monopoles; magnetni monopoli; spin ice; spinski led